Effect of Electronic Education with E-Education Applications Understanding of Nurses in Prevention Deep Vein Thrombosis - Etikasari, Elfi; Chayati, Nur (JOSING: Journal of Nursing and Health, 2022)
This study aims to determine the effectiveness of electronic education with the application of e-Education to understand nurses in preventing DVT. This research uses an experimental method with a Pre-test and Post-test Control Group Design. The results of the study in the control group using an e-education application containing DVT material in the form of e-leaflets and the Experiment group using an e-Education application containing DVT material in the form of an e-book, meaning that both groups tend to experience changes in understanding, but the proportion of respondents who study e-application e-education containing DVT material in the form of e-books tends to experience a higher increase than respondents who look e-education applications containing DVT material in the form of e-leaflets. In conclusion, using the e-leaflet e-education and the e-education e-book applications can increase nurses' understanding of DVT prevention. Keywords: DVT, Educational Electronics, Nurse Understanding